2014
DOI: 10.1128/genomea.00239-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Nitrofurantoin-Sensitive and -Resistant Escherichia coli ST540 and ST2747 Strains

Abstract: Widespread multidrug resistance in Escherichia coli has necessitated the reintroduction of older antibiotics, such as nitrofurantoin. However, mechanisms by which resistance to nitrofurantoin emerges in E. coli are not well elucidated. Toward this aim, we sequenced two nitrofurantoin-sensitive E. coli sequence types (ST540 and ST2747) and their four nitrofurantoin-resistant derivatives generated in vitro under aerobic and anaerobic growth conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…A 559-bp fragment containing the coding sequence of wild-type ribE, including 65-bp upstream and 23-bp downstream regions (GenBank accession no. CP007392; bases 1080502 to 1081060) (13), was prepared by PCR amplification, and the PCR fragment was cloned in a pCR2.1 vector by Topo TA cloning (Invitrogen, Carlsbad, CA), according to the manufacturer's protocol. The resulting recombinant vector, LMZ-pCR2.1, was electrotransformed in ST2747-an, which was made electrocompetent by successive washing steps with an ice-cold 10% glycerol suspension at log phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 559-bp fragment containing the coding sequence of wild-type ribE, including 65-bp upstream and 23-bp downstream regions (GenBank accession no. CP007392; bases 1080502 to 1081060) (13), was prepared by PCR amplification, and the PCR fragment was cloned in a pCR2.1 vector by Topo TA cloning (Invitrogen, Carlsbad, CA), according to the manufacturer's protocol. The resulting recombinant vector, LMZ-pCR2.1, was electrotransformed in ST2747-an, which was made electrocompetent by successive washing steps with an ice-cold 10% glycerol suspension at log phase.…”
Section: Methodsmentioning
confidence: 99%
“…Both ST540-p and ST2747-p, together with their mutants that showed the highest nitrofurantoin MICs aerobically (ST540-a and ST2747-a) and anaerobically (ST540-an and ST2747-an), were subjected to whole-genome sequencing (13). Full genomes were compared to identify mutations in the known resistance determinants nfsA and nfsB, as well as to check for other genomic changes indicative of as-yet-undescribed nitrofurantoin resistance determinants.…”
Section: Nit-r Mutants Generated In Vitromentioning
confidence: 99%
“…In this study, it was isolated from Jimba Oja and possibly may be a mutant variation of an Escherichia coli strain, further research is suggested on this strain as available information at this period is limited. Escherichia coli strain ST2747 and Escherichia coli strain ST540 complete genome have been proved to be antibiotic resistant (nitrofurantoin resistant) and has necessitated the introduction of older and stronger antibiotics in treating infections caused by it [28]. Escherichia coli strain EADK4 16S ribosomal RNA gene has been found to bear very close similarities with pathogenic E. coli O157:H7 which has cattle as its main reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal mutations known to be associated with resistance to fluoroquinolones in E. coli were extracted from the genome-wide SNP calls obtained previously based on mapping the reads to the E. coli strain 12009 O103:H2 reference genome 6 . These included specific mutations in the QRDR of gyrA, gyrB, parC and parE 57 , and non-synonymous substitutions in nfsA (residues [11][12][13][14][15] which confer resistance to nitrofurantoin 58,59 .…”
Section: Detection Of Snps Conferring Resistance To Fluoroquinolones mentioning
confidence: 99%